2017
DOI: 10.1016/j.ejogrb.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical activity practice and metabolic profile of postmenopausal women under treatment with aromatase inhibitors for breast cancer

Abstract: The amount of physical activity practice is inversely related to lipid profile, glucose and C-reactive protein in women without breast cancer. This relation was not observed in the cancer survivors, suggesting that the use of aromatase inhibitors could influence or low intensity of physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies investigating differences in the use of AI vs. tamoxifen have shown a higher risk of cardiovascular events in users of AI 23,24 . The use of AI may cause a decrease in the practice of PA for older women with BC 25 , and it is known that its use can lead to musculoskeletal symptoms 26 , osteoporosis and bone fractures 27 . Given the above, it is important that older women who receive AI are prescribed tailored exercises within the oncology setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating differences in the use of AI vs. tamoxifen have shown a higher risk of cardiovascular events in users of AI 23,24 . The use of AI may cause a decrease in the practice of PA for older women with BC 25 , and it is known that its use can lead to musculoskeletal symptoms 26 , osteoporosis and bone fractures 27 . Given the above, it is important that older women who receive AI are prescribed tailored exercises within the oncology setting.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature [10][11][12] age and BMI are key potential predictors adopted in studies addressing CRF, therefore age was considered a confounder for the analysis of the association between anthropometric measures and CRF. All analyses were conducted in SPSS version 25…”
Section: Methodsmentioning
confidence: 99%
“…It may be the case that aromatase-mediated E2 increases physical activity in females whereas other factors (e.g., T) are more important regulators of physical activity in males. Human studies have also shown reduced physical activity specifically among women on AI ( 164 ). This finding likely has important clinical ramifications, as physical inactivity exacerbates musculoskeletal dysfunction, as mentioned above.…”
Section: Potential Remediation Strategies For Aromatase Inhibition-rementioning
confidence: 99%